ChemInform Abstract: Benzylic C—H Azidation Using the Zhdankin Reagent and a Copper Photoredox Catalyst. Issue 32 (July 2016) - Rabet, Pauline T. G.; Fumagalli, Gabriele; Boyd, Scott; Greaney, Michael F.
Abstract: A wide range of substrates bearing various functional groups and having a primary, secondary, or tertiary benzylic position are utilized in azidation reactions for the C—N bond formation at benzylic C—H positions.